AETHRA NEXUS: DESIGN OF A BASKETBALL INTERNATIONAL ARENA IN SURABAYA CITY WITH A DECONSTRUCTIVIST ARCHITECTURE APPROACH - Femas Dwi Ramadhani; Respati Wikantiyoso; Hery Budiyanto; Junianto (ARCHITENSA : Architectural Design Journal, 2026)
The design of the “Aethra Nexus” Basketball International Arena in Surabaya is motivated by the need for an international-standard sports facility capable of strengthening the city’s identity while supporting the national basketball ecosystem. Surabaya was selected due to its strong fan base, adequate infrastructure, strategic position as Indonesia’s second-largest metropolitan city, and the active support of both government and private sectors in advancing the sports industry. This project adopts a deconstructivist architectural approach to generate an iconic form that is dynamic and expressive, while incorporating the infinity symbol (∞) as a representation of continuity, global connectivity, and limitless potential in the regeneration of athletes and sports culture. The concept also responds to critical issues such as unequal global access, excessive commercialization, athlete pressure, organizational stagnation, and gender disparities within the basketball community. Design innovation is realized through the application of sustainable design principles, the exploration of advanced materials, and the integration of a forest trail connected to an urban forest, serving as a recreational and ecological element that enhances spatial experience. This arena is expected to function as a hub for competition, collaboration, and continuous development, contributing to improved athletic performance, the growth of the creative economy, and the enhancement of Surabaya’s sports tourism appeal.